OP33 Symptomatic vs pre-symptomatic treatment of tyrosinemia type 1 with nitisinone: a systematic review. (2nd September 2017) - Stinton, C; Geppert, J; Freeman, K; Clarke, A; Fraser, H; Johnson, S; Sutcliffe, P; Taylor-Phillips, S
Abstract : Background: Tyrosinemia type 1 is a rare autosomal recessive disorder of amino acid metabolism, affecting approximately 1 in 1 00 000 people. Without treatment, death is common in childhood. Treatment with nitisinone is associated with reductions in mortality and morbidity; some studies suggest better outcomes when treatment is initiated before the symptoms of the disorder present. An apparent benefit of earlier versus later treatment has been used to support the implementation of newborn screening for Tyrosinemia type 1, but these studies have not been synthesised or quality appraised. We conducted a systematic review to examine if individuals treated following screen detection of the disorder had better outcomes than those treated following symptomatic detection. Methods: Standard systematic review methods were used. Embase, Medline, Pre-Medline, and Web of Science were searched. Participants were individuals with Tyrosinemia type 1. We compared people who received nitisinone following screen detection of the disorder (early treatment) with those who received nitisinone after symptomatic presentation (late treatment). Any reported outcomes were considered. Two reviewers independently screened and assessed records, and conducted quality appraisal (using the Quality Assessment Tool for Quantitative Studies). Data extraction was carried out by one reviewer, and checked by another. A narrative synthesis of results was carried out. Post-hoc comparisons were conducted to address confounding factors and applicability concerns. Results: The titles/abstracts of 470 unique records were examined, and 50 full texts assessed. Seven articles were included in the review. Study sample sizes ranged from 17 to 148. Methodological quality of the studies was moderate to weak. There was evidence of associations between early treatment with nitisinone and lower rates of death, liver disease and transplantations, and renal dysfunction. However, posthoc analyses suggested an association between earlier treatment and lower rates of liver transplantation but not mortality (analysis 1) or no differences in outcomes for those treated earlier versus later (analyses 2 and 3). Discussion: Evidence from observational studies suggests that treatment with nitisinone initiated during the pre-symptomatic period may be beneficial to people with Tyrosinemia type 1. However, this is subject to bias and applicability concern; the apparent benefits of early treatment may not be present when these issues are addressed. There are several challenges inherent in rare diseases research, including small and heterogeneous populations, lack of appropriate comparator treatments, and limited knowledge about the disease. Our review suggests that alternative research methods or tolerance of lower levels of evidence may be required.